Exercise program for prevention of groin pain in football players: a cluster-randomized trial - Hölmich, P.; Larsen, K.; Krogsgaard, K.; Gluud, C. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Groin injuries cause major problems in sports and particularly in football. Exercise is effective in treating adductor-related groin pain, but no trials have been published regarding the specific prevention of groin pain or prevention specifically targeting overuse injuries in sport using exercise programs. We performed a cluster-randomized trial including 55 football clubs representing 1211 players. The clubs were randomized to an exercise program aimed at preventing groin injuries (n=27) or to a control group training as usual (n=28). The intervention program consisted of six exercises including strengthening (concentric and eccentric), coordination, and core stability exercises for the muscles related to the pelvis. Physiotherapists assigned to each club registered all groin injuries. Twenty-two clubs in each group completed the study, represented by 977 players. There was no significant effect of the intervention (HR=0.69, 95% CI 0.40-1.19). The risk of a groin injury was reduced by 31%, but this reduction was not significant. A univariate analysis showed that having had a previous groin injury almost doubles the risk of developing a new groin injury and playing at a higher level almost triples the risk of developing a groin injury.